Strategi Penanganan Speech Delay pada Anak: Literatur Review - Rizqi Amaliyah; Endyka Erye Frety (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Speech delay is a speech delay with development far below normal for children of their age. According to the Indonesian Pediatrician Association (IDAI), as many as 5 - 8% of preschoolers experience speech delays. Speech and language delays or disorders are becoming increasingly common today. In Jakarta, 21% of children experience speech delay. This literature review aims to find strategies for dealing with speech delay in children. The literature used is literature published within the last 5 years (2018 to 2022) and is primary research. The keywords used in this literature search were late speech, and children. Search using the Google Scholar search engine and Portal Garuda. The results of this literature review are strategies for handling speech delay in children that can be done are to involve the child to speak in every situation, invite the child to speak slowly, use correct and appropriate language and do it repeatedly, when the child is in the process of speaking, you should pay attention and observe every word or sentence that is spoken by children, justify sentences whose pronunciation is still wrong, and stimulate children's interpersonal communication so that children are more confident when carrying out the process of communication and interaction. Children can also be invited to do storytelling activities to improve vocabulary and speaking skills.Â